DESCRIPTION OF THE LEVEL OF KNOWLEDGE AND BEHAVIOR OF DIABETES MELLITUS PREVENTION IN STUDENTS OF THE D-IV MEDICAL LABORATORY TECHNOLOGY STUDY PROGRAM, CLASS OF 2025. - Dewi Herlyana Putri; Ni Komang Eva Dwi Yanti; Ni Luh Yesi Pratami; Wandy Christiawan Lampaga; Agung Surya Rahman; Moh Arif; Saskirana; Fitri Aramadani; Novita Fitri Fajriani; Mujizat (PT. Radja Intercontinental Publishing, 2026)
Diabetes Mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin production or function. This study aimed to describe the level of knowledge about Diabetes Mellitus among students of the D-IV Medical Laboratory Technology Study Program, class of 2025. This descriptive study used a cross-sectional approach involving 34 respondents through questionnaire distribution. The results showed that 52.9% of respondents had good knowledge, 35.3% had sufficient knowledge, and 11.8% had poor knowledge. Students still showed limited understanding regarding diabetes complications and normal blood glucose levels. Overall, students demonstrated a fairly good level of knowledge about Diabetes Mellitus.